FPGA Realization of PWM using HDL - Krishna, V.V.S. Vijaya (International Journal of Computer Sciences and Engineering, 2019)
Pulse Width Modulation (PWM) is an essential technique for many electrical applications. It is mainly used for controlling DC power to an electrical device. It can be used in applications where its duty cycle is used to convey information over a communication channel. Though many software designs and hardware models are available for PWM, FPGA modules are reliable in terms of speed and complexity. Hardware optimization is possible in FPGAs. Hence work is focused to realize the PWM on FPGA. In this paper hardware model of PWM using HDL is presented. This model is designed using VHDL and implemented on VIRTEX FPGA Device. Simulation is carried using Xilinx ISE. The RTL Design is synthesized using Xilinx XST and the generated bit stream file is implemented on Virtex FPGA board.